Surface restructuring in AgCu single-atom alloy catalyst and self-enhanced selectivity toward CO2 reduction. (10th September 2022) - Wang, Hailing; Zhou, Xiangji; Yu, Tianshui; Lu, Xianglong; Qian, Lihua; Liu, Pan; Lei, Pengxiang
Highlights: Nanopporous AgCu single atom alloy catalysts are fabricated by dealloying for CO2 electroreduction. Surface reconstruction of Cu leads to a self-enhanced selectivity toward CO and an inhibition of hydrogen evolution reaction. The CO Faradic efficiency can be as high as 97.5% and stable for more than 13 h on the well-reconstructed nanoporous AgCu electrode. The restructuring of Cu experienced a spinodal decomposition process. The spinodal decomposition is driven by CO2 reduction rather than HER. Abstract: Single atom alloy catalysts, consisting of trace amount of isolated solute atoms alloyed into the host matrix, provide a promising approach to tune the electronic structure and performance of bimetallic catalysts for breaking the limits of scaling relationships based on the unique electronic structures. However, the precisely as-synthesized surface usually suffers from surface evolution leading to activity and durability decay. Herein, the understanding of surface restructuring under reaction conditions is of great importance in optimizing catalytic performance of bimetallic catalysts. In this work, on account of the surface evolution of Cu in electrochemical reactions and its limited miscibility in Ag, a nanoporous AgCu single atom alloy catalyst with atomic ratio Cu:Ag = 1:110 is fabricated by chemical dealloying process. And a CO2 -reduction-induced surface restructuring is achieved upon the well-designed catalyst. Noteworthily, nanoporous AgCu exhibits self-reinforcing selectivity toward CO2 reduction and suppressed hydrogen evolution in parallel with migration of Cu to the surface, although the charge transfer from Ag to Cu results in a strong tendency toward hydrogen evolution at the initial catalytic stage. By combining in situ electrochemical hypersensitive response to surface state with ex situ characterizations, the surface reconstruction is verified to be driven by electrochemical reduction of CO2 rather than hydrogen evolution reaction, and can be modulated by the applied potential. Well-reconstructed nanoporous AgCu facilitates the adsorption of CO2 . Electronic effect of the restructuring of Cu enhances CO desorption ability on the surface. Consequently, electronic and geometric effects synergically lead to excellent performances with CO Faradaic efficiency of 97.5%. The insights gained from the reconstruction-induced self-reinforcing behavior of bimetallic electrocatalyst shall offer an avenue to rationally design bimetallic electrocatalysts for electrochemical CO2 reduction. Graphical abstract: With the reconstruction of Cu on the surface of AgCu single atom alloy catalysts, driven by CO2 electroreduction, the Faradic efficiency of CO increased gradually until reached a stable selectivity as high as 97.5%. Image, graphical abstract